Pengaruh Struktur Modal, Likuiditas dan Ukuran Perusahaan terhadap Kinerja Keuangan pada Perusahaan Sektor Transportasi dan Logistik yang Terdaftar di Bursa Efek Indonesia Periode 2021-2024 - Muhammad Zidan; Sigit Pramono Hadi; Dadang Irawan (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study investigates the influence of capital structure, liquidity, and firm size on the financial performance of transportation and logistics sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. The research employs a quantitative approach using secondary data obtained from the annual financial reports published on the official IDX website. The analysis was conducted through a series of statistical procedures, including classical assumption tests, multiple linear regression analysis, as well as partial and simultaneous significance testing. The partial test results indicate that each of the independent variables—capital structure, liquidity, and firm size—has a significant effect on financial performance. Likewise, the simultaneous test results confirm that these three variables together play an important role in shaping company performance. These findings highlight the importance of maintaining an optimal capital structure that balances debt and equity, sustaining adequate liquidity to meet short-term obligations, and leveraging firm size as a competitive advantage. Proper management of these factors can strengthen financial stability, improve operational efficiency, and ultimately increase profitability. The results of this study provide useful insights for company managers, stakeholders, and investors in making strategic financial decisions within the transportation and logistics sector. Furthermore, the research contributes to the academic literature by reaffirming the critical role of financial management practices in determining firm performance in emerging markets such as Indonesia.